National Disaster Policy: Criticism of the State's Response to the Disaster in West Sumatra - Muhammad Zikri; Ashri Ramadhan (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2026)
The determination of national disaster status in Indonesia is frequently misconstrued as a purely technocratic decision governed by objective metrics of casualties and material loss. This article challenges that positivist assumption by analyzing the state's refusal to elevate the status of the May 2024 cold lava flood (galodo) in West Sumatra, despite catastrophic damage that exceeded regional fiscal capacities. Utilizing a Critical Policy Analysis (CPA) framework synthesized with Joel Migdal's State-in-Society theory, this study demonstrates that disaster status determination functions as a political mechanism for fiscal preservation and the management of central-regional power relations. The analysis reveals three primary policy patterns: (1) the discursive manipulation of legal definitions regarding "government paralysis" to avoid statutory obligations; (2) the deployment of "politics of survival" strategies to protect the central state budget from unlimited liability; and (3) the depoliticization of ecological causality to shield extractive political-economic interests from scrutiny. The findings indicate that the current disaster governance regime operationalizes a logic of containment that subordinates social justice to macro-political stability, effectively shifting the burden of recovery to peripheral local governments with limited resources. This article concludes that without structural reform to the legal framework specifically the objectification of disaster indicators the state will continue to perpetuate structural inequalities through discretionary exclusion